Damage of saline intact loess after dry-wet and its interpretation based on SEM and NMR - Xu, Jian; Li, Yanfeng; Ren, Chang; Lan, Wei (Soils and foundations, 2020)
In this paper, influence of dry-wet cycles on the damage characteristics was investigated on saline loess specimens by infiltrating sodium sulfate solution with different preset concentrations. Scanning electron microscope (SEM), triaxial shear tests, and nuclear magnetic resonance (NMR) were used to detect the changes in soil strength parameters and microstructure with dry-wet cycles and salt content. The SEM images show that the skeleton of saline loess at higher salt contents or after more dry-wet cycles tend to be looser, and more large and medium-sized pores appear. This implies the weakening of soil structure, as proved by the increase of both pore area ratio and fractal dimension. The cohesion and internal friction angle both decrease with dry-wet cycles, and tend to stabilize after five cycles, while the two indexes vary with salt content in a linear pattern. The cohesion-based damage ratios due to dry-wet cycles and salt weathering were discussed. The equation for NMR-based porosity was established considering both dry-wet cycles and salt content. Finally, the predictive model for damage degree based on the porosity equation was obtained, which can well predict the damage of saline intact loess under the coupled influence of dry-wet cycles and salt weathering.